Relé autoalimentado em proteção de subestações unitárias distribuídas de geração centralizada - Seifert, Rodrigo (2022)
The Brazilian market for centralized photovoltaic generation demands an equipment costs reduction, without losing operational safety and continuity. To meet this request, from prefabricated unitary substations manufacturers, is necessary to apply relays that guarantee the protection, of the equipment connected in medium voltage, regardless of the auxiliary voltage. This document present the study of self-powered relay application with medium voltage switchgear, verifying, through testing, the functioning of the self-powered relay, as well as its applicability in a centralized generation plant.